THE SIGNIFICANCE OF SIMULATION TRAINING FOR FAMILY PHYSICIANS AS A TOOL FOR OBJECTIVE SELF-ASSESSMENT - Rano K. Dadabaeva; Oybek F. Eshmamatov; Zebo I. Ruzieva; Ozoda A. Mirzabekova (Central Asian Journal of Medicine, 2023)
The article presents data on the study of the importance of simulation training for family doctors in the system of postgraduate continuing medical education. Along with the study of the professional and organizational structure of medical cadets studying at the Department of Advanced Training of Doctors of the Tashkent Medical Academy, a survey was conducted on the knowledge of using various simulators. As a result of the work carried out, it was found that the use of simulation teaching methods in the system of postgraduate education contributes to an objective self-assessment of their professional competence, which serves as a motivation for them to improve their knowledge and improve the quality of medical services in primary health care.